Medidas de Confort a pacientes con paraplejía. - Calderón Ribera, Alex Fernando (2024)
ABSTRACT: World Health Organization (WHO) defines paraplegia as paralysis of the lower limbs due to compromise of the motor pathways secondary to a spinal cord injury in the thoracolumbar segments. Currently, the National Council for Disability Equality (CONADIS) in Ecuador reported 480,776 people with disabilities. That amount represents 44.87% of physical or motor disabilities in the country. This research aims to determine the different comfort measures that are applied in patients with paraplegia, based on Katherine Kolcaba's theory. One of the facets of comfort includes the notion of assistance or support. The subjective state of those who experience relief, satisfaction of physical, mental, spiritual or sociocultural needs. Therefore, it is important to evaluate continuously each intervention administered to each patient, family or community. In fact, to face this problem, it is necessary to apply a holistic intervention providing direct care to achieve maximum independence within their conditions, promoting self-care at a social level within health care, political, governmental or social environments; additionally, to facilitate timely access to public or private spaces. Finally, we deduce that comfort care in the relationship to the patient with paraplegia is reflected as a significant challenge for the patient themselves, the family and the different health care systems.